Decreased Vacuolar Ca2+ Storage and Disrupted Vesicle Trafficking Underlie Alpha-Synuclein-Induced Ca2+ Dysregulation in S. cerevisiae - Callewaert, Geert; D’hooge, Petra; Ma, Tien-Yang; Del Vecchio, Mara; Van Eyck, Vincent; Franssens, Vanessa; Winderickx, Joris (Frontiers in Genetics, 2020)
The yeast Saccharomyces cerevisiae is a powerful model to study the molecular mechanisms underlying α-synuclein (α-syn) cytotoxicity due to the high degree of conservation of cellular processes with higher eukaryotes and the fact that this yeast does not express homologs of the human synuclein family. In this work, we focused specifically on the interplay between α-syn and intracellular Ca2+ homeostasis. Using temperature-sensitive SEC4 mutants and deletion strains for the vacuolar Ca2+ transporters Pmc1 and Vcx1, together with aequorin-based Ca2+ recordings, we show that overexpression of α-syn shifts the predominant temporal pattern of organellar Ca2+ release from a biphasic to a quasi-monophasic response. Fragmentation and vesiculation of vacuolar membranes in -syn expressing cells can account for the faster release of vacuolar Ca2+. -Syn further significantly reduced Ca2+ storage resulting in increased resting cytosolic Ca2+ levels. Overexpression of the vacuolar Ca2+ ATPase Pmc1 in wild-type cells prevented the α-syn-induced increase in resting Ca2+ and was able to restore growth. We propose that α-syn-induced disruptions in Ca2+ signaling might be an important step in initiating cell death.